The Efforts to Improve Children’s Motoric Ability By Utilizing The Role of Traditional Games - Ilham Kamaruddin; Hendy Tannady; Mia Aina (Journal on Education, 2023)
The purpose of this study was to find out the implementation of traditional games such as traditional hopscotch and jump rope games on students' gross motor skills and find out how much influence there was between experimental class 1 using traditional hopscotch games and experimental class 2 using traditional jump rope games on students' gross motor skills. This study uses a quantitative approach. This research is an experimental research with the design used is the Quasi Experimental Research method or quasi-experimental. Quasi Experimental Research is a type of research method that has a control group and an experimental group that are not randomly selected. Researchers used the Quasi Experimental Research method because in this study there were outside variables that the researcher could not control. The conclusion from this study is that there is an influence of traditional games (engklek and jump rope) on children's gross motor skills. The implication of this study is as a complement in completing the playing process for children at school in games for gross motoric skills.